ANALISIS LAPORAN ARUS KAS TERHADAP LIKUIDITAS PADA PT. KIMIA FARMA TBK - Leiwakabessy, Pitter; Kurniawati, Erna; ika, Vatika (LPPM Politeknik Saint Paul Sorong, 2021)
his study aims to determine the cash flow statement to measure the company's liquidity. At PT.Kimia Farma Tbk. This type of research is descriptive. The data used is secondary data. The data collection method used is qualitative and quantitative analysis. The data analysis technique used is To measure the company's liquidity through the cash flow statement using the operating cash flow ratio (AKO), the interest cash flow coverage ratio (CKB), the Capital Expenditure Ratio (PM), the Total Debt Ratio (TH).